Gestational Diabetes Mellitus in a Tertiary Care Hospital of Kolkata, India: Prevalence, Pathogenesis and Potential Disease Biomarkers - Basu, Jayita; Datta, Chhanda; Chowdhury, Subhankar; Mandal, Debasmita; Mondal, Nandan Kumar; Ghosh, Amlan (Experimental and Clinical Endocrinology & Diabetes, 2020)
Aims Prevalence of gestational diabetes mellitus (GDM) may vary across a country like India. Risk factors and disease-pathogenesis were also not fully elucidated. This study aimed to examine prevalence of GDM among pregnant women visiting antenatal clinic of a tertiary-care hospital of Kolkata, India; possible mechanism of disease pathogenesis and potency of associated parameters as disease biomarkers were also explored.Methods 735 pregnant women were screened for GDM according to DIPSI (Diabetes in Pregnancy Study Group India) guideline and risk-factors were analyzed. Case-control study was conducted with 114 GDM and 114 matched non-GDM control. Blood sample was collected before glucose load for complete blood count, measurement of reactive oxygen species (ROS) and assessment of DNA damage.Results Prevalence of GDM was found to be 17.2%(127/735). Maternal age, diabetic family history and acanthosis nigricans seemed to be important risk factors. Total ROS, lymphocyte DNA damage (measured by comet-assay) and some inflammatory hematological parameters were significantly higher in GDM compared to control. ROS, comet-tail DNA%, WBC, neutrophil-lymphocyte ratio (NLR) and mean platelet volume (MPV) were established as independent determinants of disease condition after adjustment for pre-gestational body mass index. In receiver operating characteristic analysis, ROS>155.7 arbitrary fluorescent unit, NLR>2.12 and MPV>11.05 fL showed 82.5 & 98.2%, 71.9 & 84.2% and 71.9 & 82.5% sensitivity & specificity respectively in disease prediction.Conclusions Prevalence of GDM seemed to be high in Kolkata on Indian scenario. Oxidative-stress, related DNA-damage and inflammation seemed to have important contribution in pathogenesis of GDM independent of obesity. ROS, NLR and MPV with respective cut-off scores might be used as diagnostic and prognostic biomarkers for better management of the disease.
Keywords: gestational diabetes mellitus; prevalence; kolkata; pathogenesis; oxidative stress; inflammatory biomarkers